Reinscribing Malinche in Contemporary Visual Art: Metaphors of Malinche at the Denver Art Museum Exhibition “Traitor, Survivor, Icon: The Legacy of la Malinche” (2022) - Kovács, Agnes (Acta Hispanica, 2023)
Malinche was an indigenous slave woman who helped Cortés communicate with and understand native chiefs during the conquest of Mexico. This paper analyzes the way the Denver Art Museum represented cultural metaphors of Malinche in visual culture in its 2022 show titled “Traitor, Survivor, Icon: The Legacy of La Malinche.” The exhibition distinguishes five key metaphors in the reception of Malinche from the sixteenth century through today. The paper highlights the theme of Malinche as the mother of the nation and its diverse appearances in visual culture among the images displayed. The paper surveys the ways in which images of motherhood interact in museum space.